THE CORRELATION BETWEEN OBESITY AND PEAK EXPIRATORY FLOW RATE CHILDREN AGE 8-12 YEARS OLD IN SARASWATI TABANAN PRIMARY SCHOOL - Ariningsih, Desak Made Wahyu; Winaya, I Made Niko; Sutadarma, I Wayan Gede (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 3 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i03.p02, 2018)
ABSTRACT                     The purpose of this study was to know correlation between obesity and peak expiratory flow rate in children. This study was done in April 2017. The design of the study was correlational with the cross-sectional method. The samples in this study were obesity children in Saraswati Tabanan primary school of 8-12 years old as many as 55 samples based on consecutive sampling technique . Based on Pearson Correlation test to determine the relationship between obesity with peak expiratory flow rates t he results showed a moderate negative association between obesity with peak expiratory flow rates of children with p = 0,000 and r = -0.524. This shows that the higher value of  BMI obesity category in children, the lower peak expiratory flow rate value is. T he results of this study shows that there was a significant relationship with moderate correlation between obesity with peak expiratory flow rate of the 8-12 year old children at Saraswati Tabanan Primary School   Keywords: obesity, peak expiratory flow rate, peak flow meter